Cytokines as Potential Therapeutic Targets for Inflammatory Skin Diseases - Numerof, R.; Dinarello, Charles A.; Asadullah, Khusru; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Cytokines and cytokine receptors remain an area of great interest for the development of targeted therapies for cutaneous inflammatory diseases. Anti-TNF therapeutics have proven to be effective in the treatment of psoriasis, and clinical investigations have now begun for other cytokine-directed therapies, such as those targeting IFN-g, IL-12p40, and IL-18. In addition to therapeutics that target cytokines directly, strategies that target cytokine signaling pathways are in development. This book summarizes the findings of the 56th International Workshop of the Ernst Schering Research Foundation that focused on "Cytokines as Potential Therapeutic Targets for Inflammatory Skin Diseases".
Inhibition of IFN-? as a Method of Treatment of Various Autoimmune Diseases, Including Skin Diseases -- Cytokine Targeting in Psoriasis and Psoriatic Arthritis: Beyond TNF? -- Inhibitors of Histone Deacetylases as Anti-inflammatory Drugs -- Dendritic Cell Interactions and Cytokine Production -- Lysosomal Cysteine Proteases and Antigen Presentation -- DCs and Cytokines Cooperate for the Induction of Tregs -- Induction of Immunity and Inflammation by Interleukin-12 Family Members -- The Role of TNF? and IL-17 in the Development of Excess IL-1 Signaling-Induced Inflammatory Diseases in IL-1 Receptor Antagonist-Deficient Mice -- TGF?-Mediated Immunoregulation -- TNF Blockade: An Inflammatory Issue -- IL-1 Family Members in Inflammatory Skin Disease -- Regulatory T Cells in Psoriasis.
Keywords: Dermatology; Allergy; Immunology; Cell biology; Dermatology; Allergology; Immunology; Cell Biology